PROGRAMS THAT TEST THEMSELVES. - Meyer, Bertrand; Fiva, Arno; Ciupa, Ilinca; Leitner, Andreas; Yi Wei; Stapf, Emmanuel (Computer (00189162), 2009)
The article discusses the AutoTest framework in software design. The entry notes that AutoTest is composed of tools that automate the testing process by using programs that contain verification instruments including Test Generation, Test Extraction, and Integration of Manual Tests. The section cites that the main focus of testing is to try to make a program fail and to be able to manage information about its failures. In relation to this, AutoTest innovates from traditional automation in the areas of test case generation, oracles and minimization.